2009
DOI: 10.1007/978-0-387-87458-6
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects models and extensions in ecology with R

Abstract: No sooner, it seems, had our first book Analysing Ecological Data gone to print, than we embarked on the writing of the nearly 600 page text you are now holding. This proved to be a labour of love of sorts-we felt that there were certain issues sufficiently common in the analysis of ecological data that merited more detailed description and analysis. Thus the present book can be seen as a 'sequel' to Analysing Ecological Data but with much greater emphasis on these very issues so commonly encountered in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
12,539
2
131

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13,696 publications
(12,704 citation statements)
references
References 0 publications
32
12,539
2
131
Order By: Relevance
“…To obtain and validate the optimal model, predictor selection was performed using the best‐subset method and based on the Akaike information criterion (AIC) value. A reasonable definition of the AIC based on mixed models is problematic (Korner‐Nievergelt, 2015; Zuur, Ieno, Walker, Saveliev, & Smith, 2009), and we therefore neglected the random effects solely for this predictor selection process, thus reducing the models to fixed effects. Model selection revealed that all the proposed predictors should be used as predictors within the final regression model.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain and validate the optimal model, predictor selection was performed using the best‐subset method and based on the Akaike information criterion (AIC) value. A reasonable definition of the AIC based on mixed models is problematic (Korner‐Nievergelt, 2015; Zuur, Ieno, Walker, Saveliev, & Smith, 2009), and we therefore neglected the random effects solely for this predictor selection process, thus reducing the models to fixed effects. Model selection revealed that all the proposed predictors should be used as predictors within the final regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we did not apply any data transformation for the three responsible variables because the relationship between responsible and explanatory variables might be changed due to data transformation. Instead, we hypothesized that the residuals of the best-fitted models are normally distributed and that the explanatory variables cause the non-normality (Zuur et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…7). Therefore, we accepted the alternative solution of Zuur et al (2009) that generalized additive models (GAMs) can cope with problems mentioned above. A linear equation can easily be extended into an additive model with multiple explanatory variables when smoothing functions are used to replace the slopes of the linear regressions:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then fit another model allowing population/varieties to have a random slope in addition to a random intercept. We compared these two models (random intercept vs. random slope and intercept) using likelihood ratio tests and the Akaike Information Criterion (Zuur, Ieno, Walker, Saveliev, & Smith, 2009). Once the best model was chosen based on the random component, we examined whether cultivated and wild individuals differed in their leaf area–stem volume allometry testing the significance of the log 10 stem volume wild/cultivated interaction term.…”
Section: Methodsmentioning
confidence: 99%